Resistencia de las resinas acrílicas de polimetil-metacrilato vs bis-acrílicas de autocurado a fuerzas de compresión - Zuñiga Paguay Yajaira Micaela (2019)
The objective of this research work was to analyze the resistance of polymethyl- methacrylate acrylic resins and bis-acrylic selfcuring to compression forces. The study was observational, descriptive, transversal and in vitro. 30 experimental units were created for the study in cylinder form with the measures established by the ISO 604 standard, which were divided into two groups, the first of 15 samples made of acrylic resin of polymethyl methacrylate (Alike) and the second group of bisacrylic resin (Protemp) following the preparation instructions and self-curing standards according to the manufacturer, were stored and subjected to compression tests with a Metrotec MTE50 series machine, in which the corresponding data were obtained to be analyzed by the SPSS statistical program. The results indicated a statistically significant difference using the Mann Whitney U test, a p value <0.05 of compression resitence was obtained between the two study groups under study, in which the first group made with Alike acrylic resin presented an average of compression maximum effort of 312.83 Mpa, wich are high values compared to those of the second group, obtaining the bis-acrylic resins (Protemp) an average of 198.33 MPa. It was determined that the Alike material based on polymethyl methacrylate has better resistance to compression